Effects of vest loading on sprint biomechanics - Brughelli, M.; Cross, M.; Zouhal, H.; Chaouachi, A. (ISBS Proceedings Archive (Michigan), 2018)
The study investigated the influence of vest loading on relative GRF`s during maximum velocity sprinting, and determined the relationship between flight times and relative vertical GRF`s. As a vertical vector-training stimulus, vest loading decreased flight times and vertical GRFs. Vertical loading does not seem to produce desirable effects on sprinting performance or GRFs.